Long-term Efficacy, Safety, and Immunogenicity of Biosimilar Infliximab After One Year in a Prospective Nationwide Cohort. Issue 11 (November 2017) - Gonczi, Lorant; Gecse, Krisztina B.; Vegh, Zsuzsanna; Kurti, Zsuzsanna; Rutka, Mariann; Farkas, Klaudia; Golovics, Petra A.; Lovasz, Barbara D.; Banai, Janos; Bene, Laszlo; Gasztonyi, Bea; Kristof, Tunde; et al.
Abstract : Background: It has been previously shown that biosimilar infliximab CT-P13 is effective and safe in inducing remission in inflammatory bowel diseases. We report here the 1-year outcomes from a prospective nationwide inflammatory bowel disease cohort. Methods: A prospective, nationwide, multicenter, observational cohort was designed to examine the efficacy and safety of CT-P13 in the induction and maintenance treatment of Crohn's disease (CD) and ulcerative colitis (UC). Demographic data were collected and a harmonized monitoring strategy was applied. Clinical remission, response, and biochemical response were evaluated at weeks 14, 30, and 54, respectively. Safety data were registered. Results: Three hundred fifty-three consecutive inflammatory bowel disease (209 CD and 144 UC) patients were included, of which 229 patients reached the week 54 endpoint at final evaluation. Age at disease onset: 24/28 years (median, interquartile range: 19–34/22–39) in patients with CD/UC. Forty-nine, 53, 48% and 86, 81 and 65% of patients with CD reached clinical remission and response by weeks 14, 30, and 54, respectively. Clinical remission and response rates were 56, 41, 43% and 74, 66, 50% in patients with UC. Clinical efficacy was influenced by previous anti–tumor necrosis factor (TNF) exposure in patients with a drug holiday beyond 1 year. The mean C-reactive protein level decreased significantly in both CD and UC by week 14 and was maintained throughout the 1-year follow-up (both UC/CD: P < 0.001). Thirty-one (8.8%) patients had infusion reactions and 32 (9%) patients had infections. Antidrug antibody positivity rates were significantly higher throughout patients with previous anti-TNF exposure; concomitant azathioprine prevented antidrug antibody formation in anti–TNF-naive patients with CD. Conclusions: Results from this prospective nationwide cohort confirm that CT-P13 is effective and safe in inducing and maintaining long-term remission in both CD and UC. Efficacy was influenced by previous anti-TNF exposure; no new safety signals were detected. Abstract : Article first published online 24 August 2017.